The Moderating Effect of the School’s Policies on School’s Characteristics and University’s Brand Equity in Viet Nam - Vuong, Bich Hang; Chi, Hsin-Kuang; Luc, Dang Anh; Yuan, Shu-Fang; Liu, Yo-Yu (International Review of Management and Marketing, 2024)
Higher education is a cornerstone of sustainable development in any nation. In Vietnam, educational policies are constantly evolving to keep pace with societal progress. The rise of private higher education and the implementation of tuition policies have contributed to improved educational quality, prompting the government to establish regulations promoting university autonomy. This study aims to determine the moderating effect of university policies on the relationship between school characteristics and brand equity. Using partial least square structural equation modeling (PLS-SEM), data from 699 respondents in Vietnam were analyzed to identify key factors linking policy to university brand equity. The findings reveal that brand equity is significantly shaped by the interaction between school policies and school characteristics, highlighting that policy, particularly those related to services, play a critical role in enhancing a university’s brand. These results suggest that universities should prioritize the clarity and strategic alignment of their service policies to strengthen brand equity. By doing so, higher education institutions can enhance their competitive advantage and better serve their stakeholders in an increasingly competitive environment.